Regulation of cell reversal frequency in Myxococcus xanthus requires the balanced activity of CheY‐like domains inFrzEandFrzZ. Issue 2 (9th February 2016) - Kaimer, Christine; Zusman, David R.
Summary: The Frz pathway of Myxococcus xanthus controls cell reversal frequency to support directional motility during swarming and fruiting body formation. Previously, we showed that phosphorylation of the response regulator FrzZ correlates with reversal frequencies, suggesting that this activity represents the output of the Frz pathway. Here, we tested the effect of different expression levels of FrzZ and its cognate kinase FrzE on M. xanthus motility. FrzZ overexpression caused a slight increase in phosphorylation and reversals. By contrast, FrzE overexpression abolished phosphorylation of FrzZ; this inhibition required the response regulator domain of FrzE. FrzZ phosphorylation was restored when both FrzE and FrzZ were overexpressed together. Our results show that the response regulator domain of FrzE is a negative regulator of FrzE kinase activity. This inhibition can be modulated by FrzZ, which acts as a positive regulator. Interestingly, fluorescence microscopy revealed that FrzZ and FrzE localize differently: FrzE colocalizes with the FrzCD receptor and the nucleoid, while FrzZ shows dispersed and polar localization. However, FrzZ binds tightly to the truncated variant FrzEΔ CheY . This indicates that the response regulator domain of FrzE is required for the interaction between FrzE and FrzZ to be transient, providing an unexpected regulatory output to the Frz pathway. Abstract : The frequency of cell reversals in the gliding bacterium Myxococcus xanthus is controlled by the Frz two‐component signaling pathway. Our experiments indicate that the response regulator domains of FrzZ positively modulate reversal frequency by counteracting the inhibitory activity of the CheY‐like domain of FrzE. Thus, the three CheY‐like domains of the Frz pathway, FrzE CheY and FrzZ CheY, CheY, constitute a regulatory unit to control the activity of the FrzE His‐Kinase, a key component of the pathway.